Pulsed administration for physiological estrogen replacement in mice [version 1; peer review: 2 approved] - Carmen Corciulo (F1000 Research Ltd, 2021)
Estrogens are important regulators of body physiology and have major effects on metabolism, bone, the immune- and central nervous systems. The specific mechanisms underlying the effects of estrogens on various cells, tissues and organs are unclear and mouse models constitute a powerful experimental tool to define the physiological and pathological properties of estrogens. Menopause can be mimicked in animal models by surgical removal of the ovaries and replacement therapy with 17β-estradiol in ovariectomized (OVX) mice is a common technique used to determine specific effects of the hormone. However, these studies are complicated by the non-monotonic dose-response of estradiol, when given as therapy. Increased knowledge of how to distribute estradiol in terms of solvent, dose, and administration frequency, is required in order to accurately mimic physiological conditions in studies where estradiol treatment is performed. In this study, mice were OVX and treated with physiological doses of 17β-estradiol-3-benzoate (E2) dissolved in miglyol or PBS. Subcutaneous injections were performed every 4 days to resemble the estrus cycle in mice. Results show that OVX induces an osteoporotic phenotype, fat accumulation and impairment of the locomotor ability, as expected. Pulsed administration of physiological doses of E2 dissolved in miglyol rescues the phenotypes induced by OVX. However, when E2 is dissolved in PBS the effects are less pronounced, possibly due to rapid wash out of the steroid.